A Global Assessment of Terrestrial Evapotranspiration Increase Due to Surface Water Area Change. Issue 3 (15th March 2019) - Zhan, Shengan; Song, Chunqiao; Wang, Jida; Sheng, Yongwei; Quan, Jiping
Abstract: Surface water, which is changing constantly, is a crucial component in the global water cycle, as it greatly affects the water flux between the land and the atmosphere through evaporation. However, the influences of changing surface water area on the global water budget have largely been neglected. Here we estimate an extra water flux of 30.38 ± 15.51 km 3 /year omitted in global evaporation calculation caused by a net increase of global surface water area between periods 1984–1999 and 2000–2015. Our estimate is at a similar magnitude to the recent average annual change in global evapotranspiration assuming a stationary surface water area. It is also comparable to the estimated trends in various components of the hydrological cycle such as precipitation, discharge, groundwater depletion, and glacier melting. Our findings suggest that the omission of surface water area changes may cause considerable biases in global evaporation estimation, so an improved understanding of water area dynamics and its atmospheric coupling is crucial to reduce the uncertainty in the estimation of future global water budgets. Plain Language Summary: Past studies have shown that global evapotranspiration has been increasing between the 1980s and 2000 and has been decreasing since 2000. These studies were done assuming surface water body areas (i.e. lakes and rivers) are constant throughout their study periods. However, surface water bodies on earth are changing constantly. Over the past 30 years, more than 90000 km3 of permanent water has disappeared while over 180000 km3 has emerged elsewhere. The conversion between land and water introduces a significant change of evapotranspiration from the earth's surface which has been neglected by past studies. Here, we quantify this change in evapotranspiration caused by such land‐water conversion to reduce the uncertainties in the estimation of global evapotranspiration trend. We find an increase in evapotranspiration caused by land‐water conversion of 30.38 {plus minus} 15.51 km3/yr between 1984‐1999 and 2000‐2015. The magnitude of this change is comparable to that of annual global evapotranspiration change assuming stationary surface water areas. Thus, surface water dynamics can lead to considerable changes in global evapotranspiration and should not be neglected in future global water budget studies. Key Points: The increase of global permanent surface water area between 1984–1999 and 2000–2015 has caused 30.38 ± 15.51 km 3 /year increase in evaporation The magnitude of this change is comparable to that of annual global evapotranspiration change assuming stationary surface water areas Surface water dynamics can lead to considerable changes in evaporation and should not be neglected in future global water budget studies